Postradiation Cranial Brachial Plexus Neuropathy: Clinical Examination and Electrophysiologic Diagnosis - Lemuel E. Gordon-Hackshaw; Nathan A. Seven; Nathan P. Young (Annals of Internal Medicine: Clinical Cases)
A muscular man in his early twenties was treated with radiation (7000 cGy in 33 fractions) for nasopharyngeal carcinoma. Seven years later, he presented with gradually progressive painless proximal right arm weakness and paresthesia, mild dysarthria, and a sensation of pharyngeal tightness. A neurologic examination demonstrated weakness and atrophy of the tongue and right upper limb with abnormal movements of the tongue. Electromyography demonstrated neurogenic limb abnormalities and tongue myokymia, confirming a diagnosis of radiation neurotoxicity.